2009
DOI: 10.1016/j.jmaa.2008.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Clique-inserted-graphs and spectral dynamics of clique-inserting

Abstract: Motivated by studying the spectra of truncated polyhedra, we consider the clique-insertedgraphs. For a regular graph G of degree r > 0, the graph obtained by replacing every vertex of G with a complete graph of order r is called the clique-inserted-graph of G, denoted as C (G). We obtain a formula for the characteristic polynomial of C (G) in terms of the characteristic polynomial of G. Furthermore, we analyze the spectral dynamics of iterations of clique-inserting on a regular graph G. For any r-regular graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…By Theorem or Corollary , it is easy to obtain the following known results after simple analyses and calculations: Let G be a r ‐regular graph. Then (1)tfalse(L(G)false)=2mn+1rmn1tfalse(Gfalse) ; (2)tfalse(L(S1false(Gfalse))false)=rmn1(r+2)mn+1tfalse(Gfalse), see Corollary 2.2 of . Let R(G) be the graph obtained from G by attaching Δd(v) pendent edges to each vertex v of G , where Δ is the maximum degree of G . Then (1)tfalse(L(Rfalse(Gfalse))false)=2mn+1normalΔnΔmn1tfalse(Gfalse), see Theorem 1.3 of . (2)tfalse(L(Sfalse(R(G)false))false)=normalΔnΔmn1(Δ+2)mn+1tfalse(Gfalse) . A bipartite graph G with bipartition (V1,V2) is called …”
Section: Main Results and Its Proofmentioning
confidence: 99%
See 2 more Smart Citations
“…By Theorem or Corollary , it is easy to obtain the following known results after simple analyses and calculations: Let G be a r ‐regular graph. Then (1)tfalse(L(G)false)=2mn+1rmn1tfalse(Gfalse) ; (2)tfalse(L(S1false(Gfalse))false)=rmn1(r+2)mn+1tfalse(Gfalse), see Corollary 2.2 of . Let R(G) be the graph obtained from G by attaching Δd(v) pendent edges to each vertex v of G , where Δ is the maximum degree of G . Then (1)tfalse(L(Rfalse(Gfalse))false)=2mn+1normalΔnΔmn1tfalse(Gfalse), see Theorem 1.3 of . (2)tfalse(L(Sfalse(R(G)false))false)=normalΔnΔmn1(Δ+2)mn+1tfalse(Gfalse) . A bipartite graph G with bipartition (V1,V2) is called …”
Section: Main Results and Its Proofmentioning
confidence: 99%
“…The number of spanning trees of line graphs and its connection to the number of spanning trees in the original graphs have been studied since 1960s via matrix manipulations and the Matrix‐Tree Theorem . Many results have been obtained, for example, [, , , ]. Recently, by an elaborate and complicated combinatorial analysis, Dong and Yan in proved the following result: truerighttfalse(L(Skfalse(Gfalse))false)=vVd(v)d(v)2×EEtfalse(G[E]false)kfalse|Efalse|false|Vfalse|+1eEEdfalse(uefalse)1+dfalse(vefalse)1.In the case of k=0, Dong and Yan showed 0truet(Lfalse(Gfalse))=vVdfalse(vfalse)dfalse(vfalse)2TscriptTfalse(Gfalse)eEEfalse(Tfalse)[]d(ue)1+d(ve)1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paraline graph, denoted by ( ), is defined as a line graph of the subdivision graph ( ) (the subdivision graph ( ) of a graph is the graph obtained from by inserting a vertex to every edge of ) of (e.g., see Figure 1). The concept of the paraline graph (or clique-inserted graph [32]) of a graph was first introduced in [25], where the author obtained the spectrum of the paraline graph of a regular graph with infinite number of vertices in terms of the spectrum of .…”
Section: Lemma 7 Let Be An ( )-Semiregular Graph With Vertices Thenmentioning
confidence: 99%
“…Such a relation was first found by Vahovskii , then by Kelmans and was rediscovered by Cvetković, Doob, and Sachs for regular graphs. They showed that if G is a k ‐regular graph of order n and size m , then tfalse(L(G)false)=kmn12mn+1tfalse(Gfalse).The first result on the relation between t(G) and t(L(S(G))) was found by Zhang, Chen, and Chen . They proved that if G is k ‐regular, then tfalse(L(Sfalse(Gfalse))false)=kmn1(k+2)mn+1tfalse(Gfalse).Yan recently generalized the result of .…”
Section: Introductionmentioning
confidence: 99%